Autoimmune Metaplastic Atrophic Gastritis: Recognizing Precursor Lesions for Appropriate Patient Evaluation. (December 2015) - Pittman, Meredith E.; Voltaggio, Lysandra; Bhaijee, Feriyl; Robertson, Scott A.; Montgomery, Elizabeth A.
Abstract : Autoimmune metaplastic atrophic gastritis (AMAG) is a significant risk factor for pernicious anemia and gastric neoplasia. Still, the histologic features of AMAG are frequently overlooked, especially in the early stages of the disease. The purpose of our study, therefore, was to catalogue the progression of histologic changes that precede the development of AMAG in affected individuals. Over a 2-year period (2012 to 2014), the diagnosis of AMAG was rendered on material from 113 patients seen at Johns Hopkins Hospital (∼1.8% of "in house" gastric biopsies). Prior gastric body biopsies had been performed on 54 (48%) patients in the cohort, and the majority of these specimens had also shown AMAG. Eighteen of the previous biopsies, however, carried a diagnosis other than AMAG: 13 inactive chronic gastritis, 2 acute Helicobacter pylori gastritis, and 1 each of eosinophilic gastritis, iron pill gastritis, and proton-pump inhibitor–like effect. Upon review of these 18 biopsies, the most common histologic findings were heavy full-thickness or deep lamina propria chronic inflammation (12), inflammatory destruction of oxyntic glands (12), metaplasia (intestinal, pyloric, or pancreatic acinar) (10), prominent lamina propria eosinophils (8), and parietal cell pseudohypertrophy (4). At least 2 of these features were present in the majority (13, 72%) of the biopsies. In addition, 7 (58%) of these patients were also found to have another autoimmune or inflammatory disorder before the diagnosis of AMAG. Although subtle, histologic features of developing AMAG are identifiable in routine gastric body biopsies. When metaplasia, full-thickness chronic inflammation, and/or oxyntic destruction are seen, a note suggesting laboratory testing and/or close clinical follow-up in this subset of patients may be warranted.